Glide and mixed climb dislocation velocity in γ-TiAl investigated by in-situ transmission electron microscopy. (15th April 2023) - Galy, Benjamin; Musi, Michael; Hantcherli, Muriel; Molénat, Guy; Couret, Alain; Spoerk-Erdely, Petra; Clemens, Helmut; Monchoux, Jean-Philippe
Abstract: Dislocation velocities at high temperatures in metallic systems are believed in literature to be different for glide and climb, the values being bigger in case of glide. However, this has not been experimentally established. Therefore, in this study, dislocation velocities were measured with simultaneous determination of the corresponding mechanism (glide or mixed climb). For this purpose, coupled experiments of measurements of dislocation velocities by in-situ TEM investigations and of determination of movement planes by stereographic analyses have been carried out at 770–790 °C in the γ phase of an intermetallic Ti-48.4Al-0.1B (at.%) alloy. Mixed climb and pure glide mechanisms have thus been identified, both leading to dislocation velocities in the same order of magnitude (in the 0.5–5 nm/s range), showing that within a transition temperature domain, mixed climb can reach the velocity of glide. Graphical abstract: Image, graphical abstract